The adherence paradox: guideline deviations contribute to the increased 5-year survival of breast cancer patients - Jacke, Christian Olaf; Albert, Ute Susann; Kalder, Matthias (BMC cancer, 2015)
In German breast cancer care, the S1-guidelines of the 1990s were substituted by national S3-guidelines in 2003. The application of guidelines became mandatory for certified breast cancer centers. The aim of the study was to assess guideline adherence according to time intervals and its impact on survival.